Modified D2 Gastrectomy operation in Gastric Cancer Patients and Outcome (Mugda Medical College Journal, 2024)
Gastric cancer remains the fifth most commonly diagnosed cancer and the third leading cause of cancer-related deaths worldwide. In 2018, there were an estimated 1,033,701 newly diagnosed cases and 782,685 related deaths. The aim of this study was to evaluate outcome of modified D2 gastrectomy operation in gastric cancer patients with or without comorbidities. This prospective observational study was conducted at the Department of Surgical Oncology, National Institute of Cancer Research and Hospital, Mohakhali, Dhaka, from July 2019 to March 2021. A total of 53 patients were included in the study. The outcome of the surgery was assessed by monitoring postoperative complications for a period of 30 days. Statistical analysis was performed using SPSS (Statistical Package for the Social Sciences) version 28. Prior to the commencement of the study, the research protocol was approved by the Research Review Committee of the Department of Surgical Oncology and the Ethical Committee of the National Institute of Cancer Research and Hospital, Dhaka. There was no significant association observed between postoperative complications of modified D2 gastrectomy and patients’ age, gender, or smoking status. Among the 53 patients, the highest proportion (92.45%) experienced anorexia, followed by vomiting (81.13%), and approximately 71.69% had dyspepsia. Among the patients, 52.83% had diabetes mellitus (DM) and 45.28% had hypertension (HTN). Patients with gastric cancer and DM were found to be more susceptible to developing wound infections. Based on the analysis of the study results, it can be concluded that modified D2 gastrectomy is a safe procedure that yields acceptable postoperative outcomes for the treatment of gastric cancer in a tertiary care center.Mugda Med Coll J. 2024; 7(1): 31-35